Measuring the impact of a place-based early years policy (SureStart) on early years outcomes using linked administrative data and a naturally occurring experiment. - Le Zhang, Meng (International Journal of Population Data Science, 2025)
Objectives Measuring the impact of a flagship early years policy (SureStart) in Northern Ireland on maternal and child health using linked administrative health data. A study pre-registration (including protocol) was completed before data access and analysis (hosted on the Open Science Framework). Methods Regression Discontinuity Design. Sure Start is a Northern Ireland programme supporting parents with young children in disadvantaged areas. Since its inception, SureStart has been expanded multiple times to include additional areas based on the index of multiple deprivation (e.g. targeting 20% most deprived areas). The expansion rule created groups of near-identical groups of areas which received Sure Start or not because they were slightly above or below the intended deprivation threshold. To measure impact, we compare outcomes for families resident in areas that were ‘close’ to the deprivation cut-off threshold using a local linear regression model. Results The presentation will report the early results of the study about the impact of SureStart on child and maternal health. Key outcomes include incidences of low birth rates, maternal obesity, breastfeeding and contact with specialist services (e.g. social work contact and hospitalisations). We do not know the exact effect sizes at this time (anticipated cleared results in summer 2025). However, our study is structured, and our outcomes, hypothesis and design are clearly stated in our study pre-registration. Conclusion Our study addresses a major evidence gap related to place-based interventions (as evidenced by recent meta-reviews). Our evidence of 'what works' (or doesn't work) is timely, as all four UK nations have strong commitments to tackling health inequalities through early years interventions and expanded early years education.